2001
DOI: 10.1109/12.926158
|View full text |Cite
|
Sign up to set email alerts
|

Symbolic analysis of bounded Petri nets

Abstract: AbstractÐThis work presents a symbolic approach for the analysis of bounded Petri nets. The structure and behavior of the Petri net is symbolically modeled by using Boolean functions, thus reducing reasoning about Petri nets to Boolean calculation. The set of reachable markings is calculated by symbolically firing the transitions in the Petri net. Highly concurrent systems suffer from the state explosion problem produced by an exponential increase of the number of reachable states. This state explosion is hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…In practice, chaining can significantly reduce the number of iterations of the BFS algorithm [15,16]. The method is specially effective if the appropriate firing order of the events is selected.…”
Section: Reachability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, chaining can significantly reduce the number of iterations of the BFS algorithm [15,16]. The method is specially effective if the appropriate firing order of the events is selected.…”
Section: Reachability Analysismentioning
confidence: 99%
“…These observations have suggested alternative traversal algorithms, named chaining [14,15]. Chaining applies the individual TRs of events in a predetermined order such that the number of new states generated at each step is maximized.…”
Section: Reachability Analysismentioning
confidence: 99%
“…Finally we should remark that a problem similar to this transition ordering arises in using transition chaining [14], a technique for speeding up BDD-based reachability analysis. The authors of [14] suggested that given a transition t, all transitions in…”
Section: Transition Orderingmentioning
confidence: 99%
“…One solution is the symbolic state space traversal by the so-called image computation elaborated by Pastor, Cortadella and Roig [7]. The algorithm builds the state space starting from the given initial state firing simultaneously all the enabled transitions from the set of the reachable states.…”
mentioning
confidence: 99%